The School for Good and Evil : The last ever after - Chainani, Soman (New York, New York : Harper, an imprint of HarperCollinsPublishers, 2016)
A handbook companion to The School for Good and Evil shares tips for surviving in the fairytale world, covering everything from surviving Uglification and picking a personal sidekick to landing a part in the school musical and navigating through fantastical kingdoms.
Welcoming -- History & lineage -- Student life -- The graduating class -- Admissions -- Frequently asked questions.
Companion to: The School for Good and Evil series, by Soman Chainani.
Ages 8 and up.
Keywords: Chainani, Soman. -- Handbooks, manuals, etc. -- Juvenile literature; Chainani, Soman -- Characters -- Handbooks, manuals, etc. -- Juvenile literature; Chainani, Soman. -- Handbooks, manuals, etc; Chainani, Soman -- Characters -- Handbooks, manuals, etc; Fantasy fiction, American -- Handbooks, manuals, etc. -- Juvenile literature; Handbooks and manuals